FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SADANIS PADA WANITA USIA SUBUR: FACTORS ASSOCIATED WITH SADANIS BEHAVIOUR IN WOMEN OF CHILDBEARING AGE - Syifa Yushallinah; Retno Hestiningsih; Nissa Kusariana; Martini Martini (Quality: Jurnal Kesehatan, 2026)
Clinical breast examinations are an early detection program to prevent breast cancer carried out by health workers. The coverage of clinical breast examinations in the working area of the Gang Aut Community Health Center is still slow. In 2021, it reached 0.1%, then increased to 6.3% in 2022, then decreased again to 2.5% from January to June 2023, with the highest number of lumps found in the 30-50 age group. Therefore, this study aimed to further examine the factors associated with clinical breast examination behavior among women of childbearing age in the working area of the Gang Aut Community Health Center. This study was an analytical observational study with a cross-sectional approach. The population in this study was 3,138, with a sample consisting of 132 women of childbearing age (30–50 years) selected using simple random sampling. Data were collected through questionnaires and interviews. The analysis used was the chi-square test. This study showed a relationship between knowledge (p-value=0.002 ; OR=3,3), attitude (p-value=0.000 ; OR=4,1), worker health support (p-value=0.000 ; OR=11,0), and self-awareness (p-value=0.000 ; OR=6,8) with clinical breast examination behavior. There was no relationship between access to health services (p-value=0.374) and family support (p-value=0.383) and clinical breast examination behavior. There was a relationship between knowledge, attitudes, support from health workers, and self-awareness with clinical examination behavior in the working area of the Gang Aut Community Health Center, Bogor City.